Meningkatkan Literasi Digital Murid Melalui Pemanfaatan Akun Belajar.Id dan Canva dalam Pembelajaran Berdiferensiasi - Siti Luthfah Ridwan (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
Differentiated learning provides opportunities for students to be able to actualize themselves in a variety of learning outcomes. Teachers can plan learning and guide and provide opportunities for students to process to become the best versions of themselves. Differentiated learning through the use of Belajar.id and Canva can be used as a solution to accommodate students’ learning needs. Differentiated learning gives students the freedom to design and create their own learning outcomes. Students have the initiative to actively participate in making learning bills. This research aims to increase students' digital literacy through the use of Belajar.id and Canva accounts in designing learning outcomes in differentiated learning. This classroom action research was carried out in 2 cycles starting from planning, implementation, observation and reflection. The research instrument is an observation sheet to observe teacher learning and students’ digital literacy skills which consist of levels of accessing, understanding, compiling and disseminating information. The research results showed that students’ digital literacy competency increased from 60.60% to 90.90% in cycle II. The implementation of learning which has implications for obtaining these results in cycle I was 85.18% and in cycle II it reached 92.60%. It can be concluded that the use of the Belajar.id and Canva accounts in differentiated learning can improve students’ digital literacy competency in environmental pollution material in class VII-D of SMP Negeri 3 Gorontalo.